Analysis of the Gut Microflora in Patients With Parkinson's Disease - Jin, Miao; Li, Jing; Liu, Fei; Lyu, Na; Wang, Kang; Wang, Lu; Liang, Shihao; Tao, Hua; Zhu, Baoli; Alkasir, Rashad (Frontiers in Neuroscience, 2019)
This study was conducted to explore the composition of the fecal microflora of Chinese Parkinson’s disease (PD) patients, as well as to explore links between PD clinical features and antiparkinsonian medications on gut microflora. 72 PD cases [59 patients suffering from PD for > 1 year (OPD) and 13 new PD (NPD) patients] were studied. Microflora communities in the feces of the patients and corresponding healthy controls were examined using high-throughput Illumina MiSeq sequencing targeting the 16S rRNA gene. The gut microflora of OPD patients contained high level of Rikenellaceae compared to corresponding HCs. In addition, significantly higher levels of Turicibacteraceae, was found in the NPD group compared to the corresponding HCs. The genera Turicibacter and Prevotella were significantly correlated with the PD severity scores. Our findings that some fecal microflora were closely related to PD clinical characteristics may enhance our understanding of the pathogenesis and treatment of PD.